“Director General Review” as a Viable Mechanism to Safeguard Malaysia’s Revenue Through Tax Justice (Journal of Science, Technology and Innovation Policy, 2024)
The Revised Kyoto Convention (RKC) serves as a guide for Customs procedures in the modern era, and Malaysia has signed on as a participating country. One crucial element of the RKC, outlined in Chapter 10 of the text of the convention, is the requirement for national legislation to include a right of appeal in Customs matters. Subsection 143(1) of the Customs Act 1967 empowers the Director General (DG) of Customs to review his own previous decisions, and the Royal Customs Malaysian Department (RMCD) has devised a systematic process referred to in this research as the "DG review." This provision was enacted to comply with the RKC's standards. Subsection 143(1) was amended in 2020 to allow aggrieved parties to submit their applications for “DG review” within 30 days from any DG decisions in the indirect taxes. Despite the amendment, no prior research has been conducted on its effectiveness. This study aims to evaluate the viability of the DG review mechanism in promoting fair and efficient tax implementation. The research employs both doctrinal legal analysis and qualitative methods to scrutinize the laws and regulations governing the right of appeal for indirect tax in Malaysia, as well as the fairness of the DG review process for taxpayers. The outcome of this study is pivotal in proposing legal solutions and validating the amended mechanism outlined in subsection 143(1) of the Customs Act 1967.
Keywords: Mechanism, Indirect Tax, Right of Appeal, Review